2017
DOI: 10.1016/j.ihj.2016.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal ventricular systolic dysfunction in patients with very severe obstructive sleep apnea: A case control study using speckle tracking imaging

Abstract: Very severe OSA is associated with significant diastolic dysfunction as well as early systolic abnormalities as evidenced by abnormal global longitudinal strain. Sleep apnea severity as measured by AHI was the only significant predictor of abnormal longitudinal strain in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
23
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 30 publications
1
23
0
4
Order By: Relevance
“…The assessment of the left ventricular systolic function, which was normal in all patients except one with a mild dysfunction, was supported with measurement of the left ventricular global longitudinal strain (GLS) [ 31 , 32 ]. Its new parameter in echocardiography, which detects subclinical cardiac involvement in different systemic diseases while systolic function is assessed by EF, is normal [ 33 35 ]. Up-to-date echocardiography experts established that the limit of normal value for this parameter is −20% [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of the left ventricular systolic function, which was normal in all patients except one with a mild dysfunction, was supported with measurement of the left ventricular global longitudinal strain (GLS) [ 31 , 32 ]. Its new parameter in echocardiography, which detects subclinical cardiac involvement in different systemic diseases while systolic function is assessed by EF, is normal [ 33 35 ]. Up-to-date echocardiography experts established that the limit of normal value for this parameter is −20% [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in LV circumferential and radial strain was revealed in moderate and severe OSA patients, but not in those with mild OSA. 7 Cho et al 8 included 25 patients with OSA and compared LV remodeling in these patients with healthy controls and obese patients, as well as the impact of bariatric surgery in patients with OSA. 6 The correlation between AHI and LV longitudinal strain and strain rates was significantly stronger than between AHI and parameters of LV diastolic function.…”
mentioning
confidence: 99%
“…LV longitudinal strain, but not circumferential strain, was found to correlate significantly with AHI. 7 Cho et al 8 included 25 patients with OSA and compared LV remodeling in these patients with healthy controls and obese patients, as well as the impact of bariatric surgery in patients with OSA. The authors did not find significant difference in LV structure (LV wall thickness and LV mass index) between obese and OSA patients, but they found significantly worse LV diastolic function in patients with OSA than in the obese and control groups.…”
mentioning
confidence: 99%
“…Regarding echocardiographic findings, many studies have found similar results. Indeed, Varghese et al [22] investigated the LV function using several parameters then compared them between patients with very severe OSA (AHI ≥ 40) and patients without OSA (control group). They found that there was no significant difference between the two groups regarding the conventional parameters of LV systolic function, including Simpson biplane LV ejection fraction and MPI.…”
Section: Discussionmentioning
confidence: 99%